THE EFFECT OF USING GALLERY WALK AS AN ALTERNATIVE TECHNIQUE TO STUDENTS’ ACHIEVEMENT IN SPEAKING - Puspitasari, Indah (Universitas Muhammadiyah Semarang, 2019)
The objective of this research was to find out whether there is a significant effect of using Gallery Walk as an alternative technique to students’ achievement in speaking. This research is a pre-experimental research using one group pre-test post-test design. The sample of the study was 25 students of X MIPA 3 in SMAN Tulakan. The data were collected by means of a speaking test. The result of the sample t-test showed that the mean difference between students’ pre-test and post-test was 5.98, with significance value was 0.05. This result showed that teaching speaking using Gallery Walk as an alternative technique had a significant effect on students’ achievement in speaking. In other words, it can be concluded that teaching speaking using Gallery Walk as an alternative technique significantly improved students’ achievement in speaking.